Prevalence of Smoking among the Students resided at Dormitories in Golestan University of Medical Sciences, Iran (Bangladesh Journal of Medical Science, 2014)
Introduction: Cigarette smoking leads to harmful physical and emotional problems and also is a predisposed factor for the addiction. The aim of this study was an attempt to determine the rate of prevalence and causes of smoking among the students of Golestan University of Medical Sciences who resided in the dormitories. Material & Methods: A cross-sectional analytical study conducted among the resident students of dormitories in 2010. The sample size consisted of all the university dormitory students. The data gathered using a validated and reliable questionnaire. The data analyzed using SPSS software and statistical tests including Chi-square, Logistic regression and Independent t-test. Results: Of 669 students, 538 (80%) of them filled out the questionnaires completely. 67.3% (362 subjects) were female. 6.1% (33 students) were smoker and 83.5% of them had experiences of cigarette smoking. The most important reasons for the smoking tendency were having a smoker friend in 33%, a personal interest 27% and as hobby in 24% of the cases. There were significant relation between age, sex, region and year of education with smoking (P0.05).Conclusion: The results indicated low prevalence of cigarette smoking among the students. However, preventive measures should be taken to conduit youth toward healthier behaviors. It seems parental control and monitoring childrens friend finding are crucial issue.DOI: http://dx.doi.org/10.3329/bjms.v13i4.16727 Bangladesh Journal of Medical Science Vol.13(4) 2014 p.460-465